Comparison of different lots of endotoxin and evaluation of in vivo potency over time in the experimental human endotoxemia model. Issue 1 (January 2019) - Kiers, Dorien; Leijte, Guus P.; Gerretsen, Jelle; Zwaag, Jelle; Kox, Matthijs; Pickkers, Peter
The experimental human endotoxemia model is used to study the systemic inflammatory response in vivo . The previously used lot of endotoxin, which was used for over a decade, is no longer approved for human use and a new Good Manufacturing Practices-grade batch has become available. We compared the inflammatory response induced by either bolus or continuous administration of either the previously used lot #1188844 or new lots of endotoxin (#94332B1 and #94332B4). Compared with lot #1188844, bolus administration of lot #94332B1 induced a more pronounced systemic inflammatory response including higher plasma levels of pro-inflammatory cytokines and more pronounced clinical signs of inflammation. In contrast, continuous infusion of lot #94332B4 resulted in a slightly less pronounced inflammatory response compared with lot #1188844. Furthermore, we evaluated whether lot #1188844 displayed in vivo potency loss by reviewing inflammatory parameters obtained from 17 endotoxemia studies performed in our centre between 2007 and 2016. Despite inter-study variability in endotoxemia-induced effects on temperature, heart rate, symptoms, and leukocyte counts, the magnitude of these effects did not decrease over time. In conclusion, although all lots of endotoxin induce a pronounced inflammatory response, the magnitude differs between lots. We observed no potency loss of endotoxin over time.